TEST METHOD OF CLT BY TENSION PERPENDICULAR TO GRAIN - Bidakov, A. M.; Raspopov, I. A. (Academic journal Industrial Machine Building Civil Engineering, 2018)
It is known that cross laminated timber (CLT) is a relatively new material in timber design. There is no information about its behavior and strength in tests by tension perpendicular to grain. Little information available is based only on simple tests for assessing the bearing capacity of some variants of devices which are used for the installation of CLT panels. In practice tension perpendicular of CLT panels occurs in curved CLT panels and in some wall-floor connections with screws. First proposed of test setup is based on the parameters related to solid timber and glulam after detailed analysis. The main influence factors on the tensile strength perpendicular to grain were investigated, and the necessary sizes of the CLT specimens were determined considering the features of the material structure. The recommendations derived in this publication can be included in standard EN 16351 or EN 408.